Peningkatan Motivasi Belajar Siswa dengan Menggunakan Aplikasi Wordwall di Kelas IV SDN Tlogosari Kulon 01 - Ahmad Ishaqie Wahdhany; Rina Dwi Setyawati; Ariani Nur Setyawati (Pascasarjana Universitas PGRI Semarang, 2024)
This research was conducted at SDN Tlogosari Kulon 01 and will discuss increasing students' learning motivation, especially in science and science subjects in grade 4 elementary school by using the wordwall application. The research method used in this research is the classroom action research method using data collection techniques, namely observation, documentation and interviews. This research was carried out in only one cycle with three meetings. The research results obtained from educator observation activities reached 83%, and student observation results reached 86% with a minimum value of 80%. Therefore, the percentage results show that using the Wordwall application can increase students' learning motivation. They look more enthusiastic, not bored and very happy when carrying out learning and evaluation assessments at the end of each lesson using the wordwall application.